2006
DOI: 10.1093/bja/ael133
|View full text |Cite
|
Sign up to set email alerts
|

The use of the GlideScope ® for tracheal intubation in patients with ankylosing spondylitis

Abstract: The GlideScope provides a better laryngoscopic view than that of direct laryngoscopy. Most of the AS patients presenting with MCLS grade III or IV by direct laryngoscopy can be intubated successfully by the GlideScope. In elective patients with AS, awake fibreoptic intubation offers a higher level of security because it can be applied while maintaining spontaneous breathing. The use of GlideScope for tracheal intubation may be an alternative option in these patients who prefer their airway management under ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(62 citation statements)
references
References 9 publications
0
59
0
3
Order By: Relevance
“…According to the fluoroscopic comparisons between GlideScope and Macintosh, GlideScope does not significantly decrease the movement of cervical spine, but improves glottic visualization in patients with MILS . Furthermore, in patients with ankylosing spondylitis, the GlideScope provided better laryngoscopic view than Macintosh and allowed nasotracheal intubation in the majority of these patients 31 25 . Key points: The application of MILS facilitates safe intubation, but makes direct laryngoscopy more difficult.…”
Section: Cervical Spine Concernsmentioning
confidence: 99%
“…According to the fluoroscopic comparisons between GlideScope and Macintosh, GlideScope does not significantly decrease the movement of cervical spine, but improves glottic visualization in patients with MILS . Furthermore, in patients with ankylosing spondylitis, the GlideScope provided better laryngoscopic view than Macintosh and allowed nasotracheal intubation in the majority of these patients 31 25 . Key points: The application of MILS facilitates safe intubation, but makes direct laryngoscopy more difficult.…”
Section: Cervical Spine Concernsmentioning
confidence: 99%
“…57 Improved intubation success rates may be seen in particular in difficult airway scenarios. Case reports, 66 case series, [67][68][69] and larger retrospective studies 60 have provided evidence that video laryngoscopes are useful as rescue devices after failed direct laryngoscopy. In one large retrospective study of Ͼ 2,000 intubations, 60 subjects were identified as potential difficult laryngoscopic intubations if they had limited mouth opening (Ͻ 3 cm) or short thyromental distance (Ͻ 6 cm), pre-existing neck pathology (mass, surgical scar, or radiation), a Mallampati score of 3 or 4, or limited neck extension or were morbidly obese.…”
Section: Rigid Video Laryngoscopesmentioning
confidence: 99%
“…Currently, patients with these deformities can be successfully treated with nasotracheal fiberoptic intubation if attempts with other techniques have failed. 26,44 As a special consideration for patients with AS, informed consent should include obtaining a consent for tracheotomy in the event that an obstructive cervical osteophyte or severe cervical flexion deformity prevent successful intubation.…”
Section: Neurosurg Focus / Volume 24 / January 2008mentioning
confidence: 99%